2018
DOI: 10.1159/000495176
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology of the Inner Ear in Charcot-Marie-Tooth Syndrome Caused by a Missense Variant (p.Thr65Ala) in the <b><i>MPZ</i></b> Gene

Abstract: Charcot-Marie-Tooth (CMT) syndrome is a clinically and genetically heterogeneous group of neuropathies affecting both peripheral motor and sensory nerves. Progressive sensorineural hearing loss, vestibular abnormalities, and dysfunction of other cranial nerves have been described. This is the second case report of otopathology in a patient with CMT syndrome. Molecular genetic testing of DNA obtained at autopsy revealed a missense variant in the MPZ gene (p.Thr65Ala), pathogenic for an autosomal-dominant form o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…In one case with a heterozygous missense variant in exon 2 of the MPZ gene (c.193A>G; p.Thr65Ala), both auditory and vestibular function were impaired. 13 In the other with a missense mutation in exon 3 of the MPZ gene (c.434A>C; p.Tyr145Ser), neither auditory or vestibular function was evaluated. 14
TAKE-HOME POINTS
→ Clinicians should consider a vestibular contribution to patients with CMT imbalance.
…”
Section: Discussionmentioning
confidence: 99%
“…In one case with a heterozygous missense variant in exon 2 of the MPZ gene (c.193A>G; p.Thr65Ala), both auditory and vestibular function were impaired. 13 In the other with a missense mutation in exon 3 of the MPZ gene (c.434A>C; p.Tyr145Ser), neither auditory or vestibular function was evaluated. 14
TAKE-HOME POINTS
→ Clinicians should consider a vestibular contribution to patients with CMT imbalance.
…”
Section: Discussionmentioning
confidence: 99%
“…Other neuropathies including Guillain-Barre syndrome (GBS), less commonly chronic inflammatory demyelinating polyradiculoneuropathy (CIDP), 26 and inherited neuropathies are associated with cerebellar pathology and vestibular neuropathy. The combination of sensorineural hearing loss (in the case of FRDA, also auditory neuropathy) and vestibular neuropathy is seen in other diseases, including FRDA, [27][28][29] Charcot-Marie Tooth (CMT) disease, 30 and Refsum disease. 31,32 In demyelinating neuropathies, vestibular dysfunction seems common.…”
Section: Neuropathymentioning
confidence: 99%
“…and human cochlea [25,26,48], including in the stria vascularis where endocochlear potential is generated, MD-DG dysfunction may affect cochlear function due to reduced endocochlear potential. Indeed, mild morphological atrophy was reported in the stria vascularis in Charcot-Marie-Tooth (CMT) disease type 1B (CMT1B), which is caused by congenital anomalies in myelination by Schwann cells [49,50]. Additionally, because SNHL in DM1 shows abnormal OAE [18,19], the same mechanism may underlie the dysfunction of Large myd/myd cochlea.…”
Section: Plos Geneticsmentioning
confidence: 99%
“…CMT1A and CMT1B are neuropathies caused by genetic abnormalities in peripheral myelin protein 22 and myelin protein zero, respectively, which are the main myelination-associated proteins in Schwann cells, and commonly show progressive SNHL starting in adolescence [75]. Although Kovach et al and Starr et al reported abnormal ABR accompanied by decreased or absent OAE [49,76], the principal pathology of CMT1B is myelin damage of the cochlear nerve initiating distally (accompanied by secondary damage of the cochlear nerve axons) without IHC loss [49,50]. While children with CMT1A showed no prolonged latency of wave I [75], adult patients showed prolonged latency of wave I [77].…”
Section: Plos Geneticsmentioning
confidence: 99%